Fatigue behavior of dissimilar friction stir welds between cast and wrought aluminum alloys - Uematsu, Y.; Tozaki, Y.; Tokaji, K.; Nakamura, M. (Проблемы прочности, 2008)
Cast aluminum alloy, AC4CH-T6, and wrought aluminum alloy, A6061-T6, werejoined by means of friction stir welding (FSW) technique. The effect of microstructure and post heat treatment on fatigue behavior of the dissimilar joints was investigated. Near the weld centre, Vickers hardness was lower than in the parent metals and the hardness minima were observed along the trace route ofFSW tool’s shoulder edge. Tensilefracture tookplace on A6061 side where the hardness was minimal, resulting in the lower static strength of the dissimilar joints than AC4CH or A6061. Fatigue fracture occurred on AC4CH side due to casting defects and the fatigue strength of the dissimilarjoints was similar to that of AC4CH, but lower than that of A6061. Friction stirprocess (FSP) andpost heat treatment successfully improved thefatigue strength of the dissimilarjoints up to that of the parent metal, A6061. Испытания на круговой изгиб для оценки сопротивления усталости проводили на воздухе и в дистиллированной воде на трех экструзивных магниевых сплавах AZ80, AZ61 и AM60 различного химического состава. На воздухе сопротивление усталости при высоких уровнях напряжений было при мерно одинаковым для всех сплавов, поскольку трещины зарождались у интерметаллических соединений Al-Mn, тогда как AZ80 с наибольшим содержанием Al имел наибольшее сопротивление усталости при низких уровнях напряжений, что объясняется зарождением трещин вследствие циклической деформации скольжения в микроструктуре матрицы. В дистиллированной воде сопротивление усталости значительно снижалось за счет образования коррозионных язв во всех сплавах, а различие в сопротивлении усталости при низких уров нях напряжений отсутствовало, указывая на то, что добавка Al, улучшавшая сопротивление усталости на воздухе, оказывала отрицательное воздействие на коррозионную усталость.